Validation of a Mathematics Teaching Assessment Scale for K-12 Basic Education: A Confirmatory Factor Analysis Approach - Madrilejos , Keith (Journal of Interdisciplinary Perspectives, 2024)
Mathematics teaching in the K-12 Basic Education Curriculum encourages educators to adopt student-centered approaches and emphasize the development of 21st-century skills. Assessing the pedagogical practices of mathematics teachers using a specific tool validated through quantitative approaches is essential to ensure the effectiveness and quality of mathematics instruction. While previous research has focused on instrument validation in various areas, including self-efficacy of math teachers, mathematics teachers’ anxiety, and online education, existing classroom observation tools have limitations, particularly in assessing public school teachers' performance specifically intended for mathematics teachers. This study aimed to validate a mathematics teaching assessment scale. The scale, constructed based on the Department of Education's classroom observation tool, initially comprised 22 items across four constructs: Mastery of the K-12 Mathematics, Teaching Methodologies, ICT Integration, and Assessment of Learning. The scale was validated through content validation, reliability testing, inter-item correlation, confirmatory factor analysis (CFA), convergent validity, and discriminant validity. A total of 687 mathematics teachers from four public schools in each of the five municipalities of the National Capital Region participated. Content validity was established by eight experts using the Scale Content Validity Index and Item-Content Validity Index, with indices exceeding 0.833, indicating validity. Each construct demonstrated desirable reliability indices based on Cronbach's alpha and composite reliability coefficients. Confirmatory Factor Analysis removed six indicators, resulting in a final scale of 16 items across four constructs. The validated instrument can effectively evaluate mathematics teachers' classroom teaching, focusing on 21st-century skills and student-centered approaches.